ANALYSIS OF THE EFFECT OF FISCAL POLICY ON THE POOR POPULATION IN INDONESIA - Nano Prawoto (SEAN Institute, 2023)
This study aims to analyze the effect of regional gross domestic product, population size, general allocation funds, regional government spending on education and health, and foreign investment in overcoming poverty in Indonesia. The model used in this research is panel data regression with the best Fixed Effect Model. The data used in this study is data sourced from the Indonesian Central Bureau of Statistics and the Ministry of Finance of the Republic of Indonesia from 2010-2020. The results of the study show that gross domestic regional income, General Allocation Fund, Health Budget, and foreign investment have an influence on the problem of poverty in Indonesia, an increase in these variables will reduce the number of poor people. An increase in population will increase the number of poor people. Meanwhile, the education budget carried out by the local government does not affect the number of poor people. The government needs to review activity programs to improve human resources through Elementary and Secondary Education throughout Indonesia.